Pembelajaran Al-Qur’an Hadist Melalui Model Accelerated Learning - Sudarmaji Sudarmaji; Muhammad Anas Maarif (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
This article aims to explain and analyze the process and implications of improving the quality of Al-Qur'an Hadith learning through the accelerated learning model. This article uses a qualitative type with a case study approach. Methods of data collection using interviews, observation, and documentation. Data analysis using inductive descriptive. The technique of data analysis is data reduction, presenting data and drawing conclusions. The results of the research from the Accelerated Learning model in improving the quality of learning Al-Qur'an Hadith at MI Darul Muttaqin show that the implementation has gone very well. This is evidenced, a) There is a preparation process, the teacher prepares the classification of student abilities and provides time outside of class hours. b) There is a delivery process that is carried out in a conducive manner, namely students listen when the teacher reads the verse. c) There is a training process, namely video playback. d) There is an appearance process, where each child who has good quality will take turns to be shown in the video. The implications of increasing the learning of Al-Qur'an Hadith through the Accelerated Learning learning model are 4 competencies (spiritual attitudes, social attitudes, knowledge and skills) that are expected to be fulfilled.